Al-Lughah al-’Arabīyah fī al-ma‘āhid al-Islāmīyah bī Indūnīsīyā: Mushkilātuhā wa ṭuruq ḥallihā - Muhammad Napis Djuaeni; Ahmadi Usman (Studia Islamika, 2021)
This article discusses the urgency of learning Arabic in Islamic boarding schools (pesantren) in Indonesia, reveals the problems, and offers suitable solutions. This study applies descriptive, historical, analytical, and library research methods by managing data from primary and secondary sources. In addition, this article also uses field studies from several pesantrens in Indonesia, starting from determining the sample to collecting data through interviews, conducting observations, filling out questionnaires, and collecting documents. This investigation found that pesantrens gave an essential position to Arabic as a tool in understanding Islamic teachings and knowledge. The problems encountered were internal in studying syntax (naḥw) and morphology (ṣarf), and external problems related to teachers, students, methods, facilities, and communities. This study offers solutions to simplify syntax (naḥw) and morphology (ṣarf) learning methods, conduct language training, enrich contrastive studies, develop linguistic curriculum, and provide facilities and communities.